Murder outside the lines ebook - Davis, Krista (Pen & Ink., 2021)
With Halloween just around the corner, the fall colors in Georgetown are brilliant. As manager of the Color Me Read bookstore, coloring book creator Florrie Fox has arranged for psychic author Hilda Rattenhorst to read from Spooktacular Ghost Stories . But the celebrity medium arrives for the event in hysterics, insisting she just saw a bare foot sticking out of a rolled-up carpet in a nearby alley. Is someone trying to sweep murder under the rug? Florrie calls in her policeman beau, Sergeant Eric Jonquille, but the carpet corpse has disappeared without a trace. Then in the middle of her reading, Hilda chillingly declares that she feels the killer's presence in the store. Is this a publicity stunt or a genuine psychic episode? It seems there's no happy medium. When a local bibliophile is soon discovered missing, a strange mystery begins to unroll. Now it's up to Florrie and Jonquille to expose a killer's true colors . . .